The Psychometric Properties of the Norwegian version of Social Responsiveness Scale (SRS) - Bergquist, Kjersti Åby; Halvorsen, Marianne Berg (PsykTestBarn, 2022)
Description: The Social Responsiveness Scale (SRS; Constantino & Gruber, 2020) is a standardized questionnaire for children aged 4–18 years. It is used as a measure of social dysfunction within the autism spectrum. International rights holders are Western Psychological Services. The Norwegian edition was originally translated into Norwegian and published for the first time in 2009. Hogrefe hold the Norwegian copyright. The questionnaire that is filled out by a parent / close person or teacher consists of 65 items divided into five sub-scales in addition to a total scale. Professionals who interpret SRS must have diagnostic competence (psychologist/medical doctor) and competence in the use of psychological tests. Literature search: Systematic literature search yielded 149 Scandinavian abstracts. Six Norwegian papers, five Swedish and one Danish paper that contained relevant psychometric data in the form of mean values, reliability, validity and sensitivity to change, met the inclusion criteria. The samples were obtained from child and adolescent psychiatric services, habilitation and special schools. Psychometrics: One study had examined the internal consistency (reliability) of the subscales. All subscales with the exception of social awareness had satisfactory internal validity. The mean values in the Norwegian and Scandinavian studies had similar values with studies outside Scandinavia. The construct validity of the SRS examined through confirmatory factor analyzes was not satisfactory. Degree of overlap between the SRS and corresponding concepts was found to be satisfactory (converging validity). Meaningful group differences emerged in SRS total scale scores between different clinical subgroups. Several treatment studies showed a significant decrease in the SRS total scale score over time, which indicates change sensitivity. Conclusion: The construct validity of the Norwegian SRS was not found to be supported through factor analyzes in a mixed sample of children and youths with developmental disorders, including autism. On the other hand, the construct validity was supported through adequate correlations with similar concepts. There were also expected scoring differences between clinical groups. The internal consistency of the majority of the subscales and change sensitivity were supported. American norms must be used with caution. There is a need for more studies of the SRS's reliability and validity in a Scandinavian context, and with special focus on the subscales since the measure is considered multidimensional.